From Teen Talk to Royal Speech: Language Style Shifts of Mia Character in The Princess Diaries - Rania Kalila Delisha; Dini Sri Istiningdias (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2025)
This study explores Mia Thermopolis's character development in The Princess Diaries through the lens of Martin Joos' theory of language styles. By examining her use of casual, formal, consultative, and intimate language, this research uncovers the complexities of her identity as she transitions from an awkward normal girl to a royal princess. The analysis highlights how Mia's language choices reflect her evolving self-acceptance and the challenges she faces in reconciling her dual identity. Mia as an awkward normal girl, establishing her as a relatable figure, with her insecurities, clumsiness, self-deprecating humor, informal dialogue, vulnerability, and her struggles. Mia is in the transition phase, highlighting her significant growth and exploration of her identity. Mia, as a Royal Princess, the contrast between her past awkwardness and her current royal responsibilities highlights the tension between her authentic self and societal expectations. Social factor plays a significant role in Mia’s Language Style. By learning to navigate the complexities of her social environment, she gains confidence in her role as a princess while remaining connected to her true self.